Age-related patterns of neophobia in an endangered island crow: implications for conservation and natural history. (February 2020) - Greggor, Alison L.; Masuda, Bryce; Flanagan, Alison M.; Swaisgood, Ronald R.
Abstract : Theory suggests that the balance between unknown dangers and novel opportunities drives the evolution of species-level neophobia. Juveniles show lower neophobia than adults, within mammals and birds, presumably to help minimize the costs of avoiding beneficial novelty, and adults tend to be more neophobic, to reduce risks and focus on known stimuli. How these dynamics function in island species with fewer dangers from predators and toxic prey is not well understood. Yet, predicting neophobia levels at different age classes may be highly valuable in conservation contexts, such as species' translocation programmes, where responses to novelty can influence the effectiveness of prerelease training and animals' survival postrelease. To better understand how neophobia and its age-related patterns are expressed in an island corvid, we surveyed object neophobia in 84% of the world's critically endangered 'alalā, Corvus hawaiiensis . Individuals repeatedly demonstrated high neophobia, suggesting that neither captivity nor their island evolution has erased this corvid-typical trait. Unexpectedly, juveniles were exceedingly more neophobic than adults, a pattern in stark contrast to common neophobia predictions and known mammalian and avian studies. We discuss the potential conservation ramifications of this age-structured result within the larger context of neophobia theory. Not only may the expression of neophobia be more complicated than previously thought but predicting such responses may also be important for conservation management that requires exposing animals to novelty. Highlights: Neophobia differs by species and is often lower in young birds/mammals than adults. Predicting neophobia levels is hard but can inform natural history and conservation. We measured object neophobia across the majority of an endangered crow species. All crows were neophobic, but juveniles were much more neophobic than adults. We discuss the reversed age effect in relation to neophobia theory and conservation.